Ensino lúdico da capoeira no ensino fundamental: análise de uma proposta realizada nas aulas de educação física - Venâncio, Washington Luiz (2024)
Capoeira manifests as an expression of popular culture, originating in a context of slavery and exploitation, which is resignified and transformed into a symbol of resistance and overcoming. However, despite its historical and cultural importance, the topic of capoeira is often neglected in the school environment, which should be a privileged space for its understanding. Faced with this scenario, there arises the need to explore capoeira more deeply as a tool for promoting positive social values, recognizing its playful and educational potential. Thus, the present study aimed to develop and analyze a playful proposal for teaching capoeira in Physical Education classes for a 1st-grade class of Elementary School. Through a Pedagogical Intervention, 10 classes were taught, involving 20 students enrolled in the first year of Elementary School in a municipal school in Guapiaçu-SP, in the first semester of 2023. Data analysis was carried out through the stages of Situated Phenomenon Analysis: reading of field notes, identification of relevant excerpts related to the researched theme, construction of analysis categories, and synthesis of understandings. The emerging categories were: A) Pre-existing conceptions of students regarding capoeira and educational interventions; B) Historical context and musicality of capoeira; C) Valuing ethnic-racial diversity through Afro-Brazilian culture and its bodily manifestation; D) Games for teaching capoeira; E) Anti-racist education; F) The issue of gender in capoeira. The results point to capoeira as a relevant educational tool, suggesting inclusive approaches and emphasizing active student participation. Additionally, they highlight the importance of musicality and activities adapted to the context of capoeira, explored through playfulness, as well as reflection on gender issues, evidencing challenges in the inclusion of women. These understandings open perspectives for a more comprehensive and transformative education, capable of contributing to the construction of a more equitable and empathetic society, highlighting the complexity and relevance of the topic for future research and pedagogical practices.